Pilot Program to Improve Self-Management of Patients with Heart Failure by Redesigning Care Coordination - Jessica D. Shaw; Daniel J. O'Neal; Kris Siddharthan; Britta I. Neugaard (Hindawi Limited, 2014)
Objectives. We tested both an educational and a care coordination element of health care to examine if better disease-specific knowledge leads to successful self-management of heart failure (HF). Background. The high utilization of health care resources and poor patient outcomes associated with HF justify tests of change to improve self-management of HF. Methods. This prospective study tested two components of the Chronic Care Model (clinical information systems and self-management support) to improve outcomes in the self-management of HF among patients who received intensive education and care coordination during their acute care stay. A postdischarge follow-up phone call assessed their knowledge of HF self-management compared to usual care patients. Results. There were 20 patients each in the intervention and usual care groups. Intervention patients were more likely to have a scale at home, write down their weight, and practice new or different health behaviors. Conclusion. Patients receiving more intensive education knew more about their disease and were better able to self-manage their weight compared to patients receiving standard care.